2013
DOI: 10.5772/55162
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Stability of Limit Cycle Walking Model with Feet: Parameter Study

Abstract: In this paper, two kinds of feet, namely, curved and flat feet, are added to limit cycle walking model to investigate its stability properties. Although both models are already proposed and are investigated, most previous works are focused on efficiency and gait behaviors. Only the stability properties of the simplest walking model conceived Garcia et al. are well defined. Therefore, there is still a need for a precise research on the effect of feet, especially in the view of local stability, bifurcation route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Some researchers have tried different ways to solve these problems. Jeon et al selected the DOI of the simplest biped walker by calculating its theoretical falling boundary [14], but this method was difficult to apply for those complicated biped walkers which had complex falling boundaries. Zhang et al proposed a bisection method to quickly determine the approximate edge of the simplest passive biped walker's DOA, but this method must know the fixed point at the beginning and the obtained edge was too rough [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have tried different ways to solve these problems. Jeon et al selected the DOI of the simplest biped walker by calculating its theoretical falling boundary [14], but this method was difficult to apply for those complicated biped walkers which had complex falling boundaries. Zhang et al proposed a bisection method to quickly determine the approximate edge of the simplest passive biped walker's DOA, but this method must know the fixed point at the beginning and the obtained edge was too rough [15].…”
Section: Introductionmentioning
confidence: 99%
“…Through both simulations and experiments, Mizuno et al 19 demonstrated that energy storage device such as a spring or rubber placed between two legs can improve the walking stability of a compass-like PDW walker. Recently, Jeon et al 20 demonstrated that the size of BoA of the simplest walking model with rolling foot or flat foot is small and the maximum slope angle and walking speed that can form stable walking are also very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers proposed a simple search algorithm to find a set of the initial conditions that result in stable limit cycles for various parameter values. 18 Recently, Jeon et al 19 applied falling boundary and energy balance line to estimate the proper initial conditions. These set of initial conditions are within the basin of attraction of the stable gait cycle.…”
Section: Introductionmentioning
confidence: 99%